Kolaborasi Manifestasi Komunikasi â€œKiai Kampoengâ€: Komunikasi Politik Kiai NU Masa Pendudukan Jepang - Kholid Mawardi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Emotional, cultural, and ideological vicinity between kiai kampoeng and NU’s grassroots community hasmade kiai kampoeng have good sensitivity to them. At Japan occupation era, when NU’s grassroots community in villagearea experience extreme suffering, kiai kampoeng share that experience. Therefore, collaboration with Japan militarygovernment is the best way chosen by kiai kampoeng to perform their religious tradition and saving NU’s grassrootscommunity from suffering.